KONVERSI KONVERSI BIOGASOLIN DARI RESIDU MINYAK PALM OIL MILLS EFFLUENT (POME) DENGAN BANTUAN IRADIASI ULTRASONIK DAN PERENGKAHAN KATALITIK - Agus Sundaryono,Arsela Eko Listiono, M. Lutfi Firdaus, Dewi Handayani (Department of Agroindustrial Technology, Bogor Agricultural University, 2018)
Palm oil mill effluent (POME) is a liquid waste by product of fresh fruit bunches processing (FFB) in palm oil factory (POF). POME contains oil residue of 0.7% (from treated FFB). The purpose of this study was to convert oil residue of POME into biogasolin with the help of ultrasonic irradiation and catalytic cracking. The convertion was performed by reacting oil residue of POME with methanol in an esterification and transesterification reaction with the aid of ultrasonic irradiation. The reaction product was further reacted in the catalytic cracking reaction using zeolite-based catalysts (Ni/HZa and Mo-Ni/HZa). The overall reaction results were characterized using GCMS to determine the constituent components. The components found using Mo-Ni/HZa catalyst were 51.22% biogasoline and other products of kerosene and diesel as well as long chain methyl ester components, whereas using Ni/HZa catalyst was found a component equivalent to diesel at 2.44%.Keywords: biogasoline, ultrasonic irradiation, catalytic cracking, zeolite catalyst, POME